Methodological proposal for determining the degree of essentiality and annual utilization factor for military vessels (2025)
To implement a precise maintenance plan aligned with ILS criteria in the naval domain, specifically in military vessels, it is essential to use methodologies that facilitate the categorization of numerous elements. The Annual Utilization Factor (FUA) and the Essentiality Grade (GRES) are key methodologies in the maintenance of military ships. FUA calculates the Annual Operation Rate (AOR) of the equipment, optimizing its use and preventing failures. GRES evaluates the importance of critical components through the Essentiality Code (MEC), guiding resource allocation and risk management. These methodologies, together, improve operational availability, optimize resources, prevent unplanned downtime, and facilitate efficient maintenance planning and informed decisions. The document describes the implementation of these methodologies in a software tool. Conceptual designs were developed, and the theory consulted on FUA and GRES was applied. After defining the characteristics and operational requirements, the program’s functionality was tested with a case study (Archangel 65 Boat) provided by the company, obtaining results that validate the program’s effectiveness. The report highlights the implementation of the FUA (Annual Utilisation Factor) and GRES (Degree of Essentiality) methodologies in military vessels, together with the presentation of a computer program developed in Python to facilitate its application. The needs, objectives, requirements, operating environment, scope and limitations of the project are detailed. In addition, the process followed by the team, from conceptual design including identification of functional requirements and evaluation of alternatives, to the creation of the first conceptual schematic, is fully explained. It describes the detailed design, which addresses the initial structure of the program and the changes made to it, and leads to the final prototype of the software, including the tests performed and the results obtained.